Legacy of the Bracero Program: Shaping US-Mexico Relations and Labor Immigration Policies - Tóth, Szimonetta (Pécs journal of international and European law, 2025)
The Bracero Program, which ended over six decades ago, remains a defining era in the US- Mexico history. Not only did this bilateral labor agreement bring cooperation and conflict between the two states, but it influenced the modern labor legislation changes in the United States. This paper examines the legacy of the Bracero Program, its influence on the 21stcentury U.S. immigration policies, and its contribution to the discourse on labor rights. One of its key outcomes was the emergence of the H-2A visa program, which continues to be a focal point in immigration debates—particularly under the second Trump administration, which seeks to impose stricter immigration controls while simultaneously proposing limited exceptions for foreign-born agricultural workers. This paper seeks to reveal the differences in the practical applications of U.S. immigration and labor policies across two distinct eras. The paper also seeks to explore how the legacy of the Bracero Program influenced current U.S. immigration and labor policies, particularly when compared to the second Trump administration's strategies for addressing agricultural labor shortages.